CYP17 genetic variation and risk of breast and prostate cancer from the National Cancer Institute Breast and Prostate Cancer Cohort Consortium (BPC3). - Setiawan, V; Schumacher, F; Haiman, C; Stram, DO; Albanes, D; Altshuler, D; Berglund, G; Buring, J; Calle, E; Clavel-Chapelon, F; Cox, D; Gaziano, J; et al. (2007)
CYP17 encodes cytochrome p450c17alpha, which mediates activities essential for the production of sex steroids. Common germ line variation in the CYP17 gene has been related to inconsistent results in breast and prostate cancer, with most studies focusing on the nonsynonymous single nucleotide polymorphism (SNP) T27C (rs743572). We comprehensively characterized variation in CYP17 by direct sequencing of exons followed by dense genotyping across the 58 kb region around CYP17 in five racial/ethnic populations. Two blocks of strong linkage disequilibrium were identified and nine haplotype-tagging SNPs, including T27C, were chosen to predict common haplotypes (R(h)(2) >or= 0.85). These haplotype-tagging SNPs were genotyped in 8,138 prostate cancer cases and 9,033 controls, and 5,333 breast cancer cases and 7,069 controls from the Breast and Prostate Cancer Cohort Consortium. We observed borderline significant associations with prostate cancer for rs2486758 [TC versus TT, odds ratios (OR), 1.07; 95% confidence intervals (95% CI), 1.00-1.14; CC versus TT, OR, 1.09; 95% CI, 0.95-1.26; P trend=0.04] and rs6892 (AG versus AA, OR, 1.08; 95% CI, 1.00-1.15; GG versus AA, OR, 1.11; 95% CI, 0.95-1.30; P trend=0.03). We also observed marginally significant associations with breast cancer for rs4919687 (GA versus GG, OR, 1.04; 95% CI, 0.97-1.12, AA versus GG, OR, 1.17; 95% CI, 1.03-1.34; P trend=0.03) and rs4919682 (CT versus CC, OR, 1.04; 95% CI, 0.97-1.12; TT versus CC, OR, 1.16; 95% CI, 1.01-1.33; P trend=0.04). Common variation at CYP17 was not associated with circulating sex steroid hormones in men or postmenopausal women. Our findings do not support the hypothesis that common germ line variation in CYP17 makes a substantial contribution to postmenopausal breast or prostate cancer susceptibility.